2019
DOI: 10.1371/journal.pone.0211469
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of sensation on the experience of a hand: A qualitative case series

Abstract: BackgroundThe experience of upper limb loss involves loss of both functional capabilities and the sensory connection of a hand. Research studies to restore sensation to persons with upper limb loss with neural interfaces typically measure outcomes through standardized functional tests or quantitative surveys. However, these types of metrics cannot fully capture the personal experience of living with limb loss or the impact of sensory restoration on this experience. Qualitative studies can demonstrate the viewp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…Whereas certain modes of pulse modulation have been described to transform paresthesia to more natural qualia 6 , these www.nature.com/scientificreports/ findings have not been replicated yet 48 . However, in addition to the aforementioned paresthetic sensations, our subjects also reported more natural sensations such as "pressure" and "touch", which agrees with reports by other groups 42,44,45,49,50 . The presence of sensations recognizable as natural might be the cause for subjects reporting a "possibly" or "almost" natural experience 51 .…”
Section: Discussionsupporting
confidence: 92%
“…Whereas certain modes of pulse modulation have been described to transform paresthesia to more natural qualia 6 , these www.nature.com/scientificreports/ findings have not been replicated yet 48 . However, in addition to the aforementioned paresthetic sensations, our subjects also reported more natural sensations such as "pressure" and "touch", which agrees with reports by other groups 42,44,45,49,50 . The presence of sensations recognizable as natural might be the cause for subjects reporting a "possibly" or "almost" natural experience 51 .…”
Section: Discussionsupporting
confidence: 92%
“…As such, the implanted electrodes seem to have raised both patients' confidence in and expectations for the degree of control they can expect of their prostheses. Previous studies have suggested that distrust or degrees of caution and risk aversion toward limb prostheses could be due to early adoption or ongoing device development (Graczyk et al, 2019). This was not observed in our participants owing potentially to the reliability and long-term stability of the neuromusculoskeletal prosthetic system when used unsupervised in daily life.…”
Section: Discussionmentioning
confidence: 61%
“…The ambiguity surrounding the use of the word "natural" underscores the importance of identifying what such generalized descriptors mean to participants in different contexts. Previous qualitative studies invoking the term "natural" with regard to describing sensory feedback have not differentiated between these multiple contexts and possible nuances in meaning (Graczyk et al, 2019). This suggests the need for ongoing research on the various possible meanings of the term "natural" and the importance of precision when using it in qualitative and quantitative research on artificially elicited sensation.…”
Section: The Descriptor "Natural" Carries Different Meanings For Partmentioning
confidence: 99%
See 1 more Smart Citation
“…And the number much more in other countries .However, about 21% of handicaps with upper limb loss disability don't use any artificial arm because they think it does not provide their needs. About 85% of them consider the lack of sensation as a factor to their think [2]. As a result of these, researchers interesting increases to reach better results to enhance the functionality of the artificial limbs.…”
Section: Introductionmentioning
confidence: 99%